“Fürchten oder Lieben?” Zu Sophokles, Oidipus Tyrannos, Vers 11 - Holzhausen, Jens (Hyperboreus, 2015)
The paper tries to show, how line 11 in “Oedipus Tyrannus” is supposed to be understood: The protagonist asks the youngsters and the priest, who have come to implore help, about their attitude towards him, if they either fear him or love him like a father. Oedipus’ self-centered view of himself can be found throughout the Prologue. It is rooted in the deep insecurity of an orphaned man, who misses his parents and for whom the impression on others is vital and an integral part of his thoughts and feelings. This insecurity and the fear of damaging his prestige explain his outbursts of rage and fury later on. Thus, to the picture of a man who is self conﬁdent and reached the peak of his power at the beginning of the play a new nuance has to be added.